Strategi Komunikasi Membangun Citra Karang Taruna Desa Berbek Sidoarjo Melalui Instagram - Dian Eka Safitri; Moch.Arkansyah (LPPM Stikosa-AWS, 2022)
Youth Organization Berbek Village (Kartar Berbek) is a social organization formed to establish a sense of brotherhood, as well as a forum for young people to develop themselves. However, during its journey, Kartar Berbek had a negative image from the community because it was considered an organization that was only active in certain activities and was considered the same as other mass organizations that only took personal benefits. The purpose of this study was to determine the Communication Strategy Youth Organization Berbek Village Building Image on Instagram. This study uses a descriptive qualitative approach. Researchers get data by conducting interviews, observations, and documentation. The resource persons in this study were the Kartar Berbek Management starting from the chairman, members, and people who have been holding Instagram social media accounts and followers. Results Based on research in the field that kartar berbek uses the stages of the AIDDA concept of Attention, Interest, Desire, Decision, and action concepts by determining content and utilizing existing features to building image on instagram so that it can increase the number of members and Instagram Kartar Berbek social media is considered very helpful and makes it easier for people to find information.